Trend Topic in School-based Lesson Study for Learning Community in Transformational Program - Reni Marlina; Hamdani Hamdani (Postgraduate, University of Mataram, 2023)
Implementation of lesson study encourages Reflective Practitioners to get used to collaborating in learning practice. In Indonesia, educational programs have been designed with collaboration in mind, promoting a reflection process within the learning community. This research focuses on trending topics/themes of reflective practitioners in supporting the sustainability of their learning communities. The participants involved in this study were 75 reflective practitioners consisting of school principals (P), school supervisors (SS), and learning committee teachers (T). Through the Facilitating School Program (FSP) Questionnaire, information was obtained that two topics were becoming trends by all reflective practitioners in Learning Community for Reflective Practitioners (LCRP) activities in schools, namely, commitment to improving quality sustainably 85.3% and conducting research collaboratively 841%. Schools must collaborate with teachers and principals to design straightforward school programs so that these two topics can be implemented smoothly